THE SOCIAL IMPACT OF GLOBALISATION ON INDIGENOUS NIGERIA LANGUAGES AND PATTERNS OF DRESSING - Okaka, Emmanuel Obukovwo; Omoyibo, Kingsley Ufuoma (EBSU Journal of Social Sciences and Humanities, 2022)
Tune to any radio or television station in Nigeria, you will imagine you are in western country because of the type of music and the manner it is aired., Globalisation has opened up international trade, which has helped many countries grow far more quickly than they would otherwise have done, and has assisted to stem the tide of poverty and hunger, reverse the spread of AIDS. But many see globalisation as a problem due to cultural diffusion of literature, music, clothing, food and traditional values and this has led some to conclude that Africa is losing its cultural identity. Six hundred and fifty-three respondents were interviewed using structured questionnaires to ascertain the social impact of globalisation, the data indicated that sixty-seven per cent of the survey group would prefer western type of dresses to African dresses, while sixty per cent of the group could not speak their mother tongue fluently. This shows the extend globalisation has impacted on our languages and dressing patterns.